Cognitive Behavioral Therapy (CBT) dalam Konseling: Tinjauan Komprehensif Teori, Teknik, dan Aplikasinya dalam Konteks Pendidikan di Indonesia - Fakhriatul Miladiah; Amirah Diniaty (Jurnal Bimbingan dan Konseling Pandohop, 2026)
Cognitive Behavioral Therapy (CBT) is an evidence-based counseling and psychotherapy approach widely used to address various psychological problems. This article aims to provide a comprehensive review of CBT, covering its historical development, basic assumptions, core concepts, main techniques, session structure, application in educational counseling services, and empirical evidence supporting its effectiveness. This study employed a narrative literature review by examining relevant Indonesian and English scholarly sources, particularly publications from the last ten years. The findings indicate that CBT has a strong theoretical foundation, structured intervention procedures, and flexibility for addressing students’ psychological and educational problems, such as anxiety, mild depression, academic procrastination, and cognitive distortions. In addition, third-wave CBT developments, including Acceptance and Commitment Therapy (ACT), Dialectical Behavior Therapy (DBT), and Mindfulness-Based Cognitive Therapy (MBCT), have expanded the application of CBT in counseling services. However, implementing CBT in Indonesia requires cultural adaptation to align with students’ social, spiritual, and contextual characteristics. Therefore, CBT can be considered a relevant, flexible, and potential counseling approach to strengthen guidance and counseling services in Indonesian educational settings.